Rock Mass Characterization using Rock Mass Rating and Encountered Geological Problems in TRT’s Component of Tehri Pumped Storage Plant, Uttarakhand, India (Hydro Nepal: Journal of Water, Energy and Environment, 2018)
As an integral part of Tehri Hydro Power Complex (HPC) located in the state of Uttarakhand in Northern India; an underground 4x250 MW Tehri Pump Storage Plant (PSP) parallel and close to the existing 1000 MW Tehri Hydro Power Plant (HPP). Tehri PSP is located on the left bank of Bhagirathi River in the district of Tehri about 1.5 km downstream of its confluence with River Bhilangana. The major project components are machine hall, upstream surge shafts, Butterfly valve chamber (BVC), Penstock assembly chambers (PAC), downstream Surge Shafts, a pair of Tail Race Tunnels (TRTs) and outlet structures are in construction stage. During underground excavation, one of the important aspects for a speedy and safe excavation is to characterize rock mass for its stand up time. Case history of Himalayan tunnel reveals that Barton’s & Bieniawski’s classification system provide better assessment of the rock mass behavior. In TRTs of Tehri PSP, Rock Mass Rating (RMR) classifications were implemented during excavation and based on their ratings, rock mass was supported. Construction stage geotechnical assessments were made, and suitable remedies were adopted for all the components of the project after geological traverses, detailed geological mapping, drift logs and logging of cores was done. This paper deals with rock mass characterization of underground structures specially in TRT’s using RMR classification and encountered geological problems during excavation.HYDRO Nepal JournalJournal of Water, Energy and Environment Issue: 23Year: 2018